2017
DOI: 10.3389/fnagi.2017.00306
|View full text |Cite
|
Sign up to set email alerts
|

Atrophy of the Posterior Subiculum Is Associated with Memory Impairment, Tau- and Aβ Pathology in Non-demented Individuals

Abstract: Alzheimer’s disease (AD) is associated with atrophy of the cornu ammonis (CA) 1 and the subiculum subfield of the hippocampus (HC), and with deficits in episodic memory and spatial orientation. These deficits are mainly associated with the functionality of the posterior HC. We therefore hypothesized that key AD pathologies, i.e., β-amyloid and tau pathology would be particularly associated with the volume of the posterior subiculum in non-demented individuals. In our study we included 302 cognitively normal el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 60 publications
5
25
0
1
Order By: Relevance
“…The topography of this progression is similar to the progression of brain atrophy, supporting a direct relationship between tau pathology and atrophy. Indeed, a number of studies have associated volumetric magnetic resonance imaging (MRI) with either pathological, 10–12 cerebrospinal fluid (CSF), 13–15 or positron emission tomography (PET) 16–18 measures of NFT burden.…”
Section: Introductionmentioning
confidence: 99%
“…The topography of this progression is similar to the progression of brain atrophy, supporting a direct relationship between tau pathology and atrophy. Indeed, a number of studies have associated volumetric magnetic resonance imaging (MRI) with either pathological, 10–12 cerebrospinal fluid (CSF), 13–15 or positron emission tomography (PET) 16–18 measures of NFT burden.…”
Section: Introductionmentioning
confidence: 99%
“…The subiculum mediates various aspects of behavior including spatial and declarative memory, contextual fear memory, memory retrieval, discrimination of complex scenes, temporal control of behavior, and motivated behavior (Gabrieli et al, 1997; Maren, 1999; O'Mara et al, 2009; Hodgetts et al, 2017; Roy et al, 2017; Cembrowski et al, 2018). In humans, it is involved in both normal cognitive function and in diseases characterized by impaired cognition including schizophrenia and Alzheimer’s disease (Carlesimo et al, 2015; Haukvik et al, 2015; Lindberg et al, 2017; Zammit et al, 2017). The subiculum is organized in both proximal-distal and dorsal-ventral directions, with heterogenous inputs and outputs, cell types, cytoarchitecture, contributions to behavior, and gene and protein expression along each axis (O'Mara, 2005; O'Mara et al, 2009; Kim and Spruston, 2012; Honda and Ishizuka, 2015; Ishihara and Fukuda, 2016; Tang et al, 2016; Roy et al, 2017; Cembrowski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As spatial disorientation is an early and common symptom of AD, the relationship between navigational strategy and the detection of pathological aging patterns needs to be explored in future work (Coughlan, Laczó, Hort, Minihane, & Hornberger, ). Recent research has found that atrophy of the pHPC in cases of MCI and AD is associated with tau‐pathology, Aβ‐pathology and declines in verbal and spatial memory (Lindberg et al, ; Llado et al, ), whereas nonpathological aging has generally been associated with mid‐ or anterior, but not posterior, volume reductions (Malykhin, Huang, Hrybouski, & Olsen, ; Rajah, Kromas, Han, & Pruessner, ; Ta et al, ). Thus, changes to pHPC/aHPC volume ratios could potentially serve as indicators of MCI or AD vulnerability, and accompany changes in spatial memory and navigation strategy.…”
mentioning
confidence: 99%